Neanderthals of Porto Selvaggio in southern Italy: lithic industry of Grotta Torre dell'Alto (Nardò, Lecce). (18th October 2021) - Ranaldo, Filomena; Massafra, Dario; Kitagawa, Keiko
ABSTRACT: Porto Selvaggio in southern Italy is where the Uluzzian culture was first identified and documented, providing key insights into the transition from the Middle to the Upper Paleolithic. The area has also yielded evidence for continuous occupations by Neanderthals spanning between Marine Isotope Stage (MIS) 5 and 3. Situated in the Natural Regional Park of Porto Selvaggio, different sites were excavated by Borzatti von Löwenstern in the 1960 and 1970s. As one of the initiatives in the research program of the Museo della Preistoria di Nardò, we have revisited the artifact assemblages from these caves. Based on the lithic analysis of production sequences, we document the development of Levallois and laminar methods before MIS 3 when this form of reduction sequence presumably dominated in the region according to the previous research. The review of the lithic assemblages is combined with the contextualization of chronostratigraphy and paleoenvironmental study in the region to consider the possible role that this region had for Neanderthals during unfavorable climatic conditions.